Estabilização de suspensões aquosas à base de biosilicato - Silva, Lucas do Carmo (Universidade Federal de São Carlos, 2023)
Aqueous suspensions based on particulate bioglasses are frequently used for the production of bioactive glass-ceramic scaffolds. Scaffolds are macroporous structures (with pores between 100 μm and 300 μm) intended for the replacement and repair of flaws in human tissues, something that is possible due to the fact that these structures favor cell penetration and increase vascularization. However, the solubilization of the glass in aqueous media favors the flocculation of the suspension. The effect of this is the compromise of process reproducibility, mechanical properties and the loss of particulate matter. Therefore, it is important to control rheology and stabilize suspensions to prevent flocculation from occurring. Thus, the present study aimed to stabilize aqueous suspensions based on Biosilicate® particles (designated here as BioS), based on electrostatic, steric and electrosteric stabilization mechanisms. For this purpose, the pH of suspensions with different weight concentrations of solids (2.5%, 5.0%, 10.0%, 20.0% and 30.0%) was measured. The use of different dispersants was not able to stabilize the suspensions with 30%w of BioS. As for the suspension of 2.5%w of BioS, the best average zeta potential value was -45 mV, obtained by adding 1.0%w of PAA. Furthermore, there was an attempt to adjust the pH of the 30%w BioS suspension using HCl. Finally, these suspensions were submitted to a qualitative sedimentation test in 25ml graduated burettes, which verified the effectiveness of using 1.0%p of PAA in the stabilization of suspensions of 2.5%p of BioS.
Stabilization of aqueous suspensions based on biosilicate
Keywords: Estabilização; Suspensões aquosas; Biovidro; Potencial zeta; Stabilization; Aqueous suspensions; Bioglass; Zeta potential; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura